Secondary-School Science Programs: Appraisal and Recommendations. - Audrieth, Ludwig F.; Burnett, R. Will; Fuller, Harry J. (Education Digest, 1958)
The article discusses appraisal and recommendations for secondary-school science programs in improving science programs in Illinois schools. The standard requirement is for one year of high-school science. Some schools require two years; a few, none. National data indicate that most students take general science and/or biology. Illinois students are believed to follow this same general pattern. Among the other science and science-related courses offered in many schools are: senior science in many schools for less capable students; a variety of applied courses such as photography and aviation. Earth science is increasingly offered, and a few schools have advanced biology, botany, or zoology.